The effect of Omega-3 polyunsaturated fatty acid supplementation on exercise-induced muscle damage - Yvoni Kyriakidou; Carly Wood; Chrystalla Ferrier; Alberto Dolci; Bradley Elliott (Journal of the International Society of Sports Nutrition, 2021)
Background Exercise-induced muscle damage (EIMD) results in transient muscle inflammation, strength loss, muscle soreness and may cause subsequent exercise avoidance. Omega-3 (n-3) supplementation may minimise EIMD via its anti-inflammatory properties, however, its efficacy remains unclear. Methods Healthy males (n = 14, 25.07 ± 4.05 years) were randomised to 3 g/day n-3 supplementation (N-3, n = 7) or placebo (PLA, n = 7). Following 4 weeks supplementation, a downhill running protocol (60 min, 65% V̇O2max, − 10% gradient) was performed. Creatine kinase (CK), interleukin (IL)-6 and tumour necrosis factor (TNF)-α, perceived muscle soreness, maximal voluntary isometric contraction (MVIC) and peak power were quantified pre, post, and 24, 48 and 72 h post-EIMD. Results Muscle soreness was significantly lower in N-3 vs PLA group at 24 h post-EIMD (p = 0.034). IL-6 was increased in PLA (p = 0.009) but not in N-3 (p = 0.434) following EIMD, however, no significant differences were noted between groups. Peak power was significantly suppressed in PLA relative to pre-EIMD but not in N-3 group at 24 h post-EIMD. However, no significant difference in peak power output was observed between groups. MVIC, CK and TNF-α were altered by EIMD but did not differ between groups. Conclusion N-3 supplementation for 4 weeks may successfully attenuate minor aspects of EIMD. Whilst not improving performance, these findings may have relevance to soreness-associated exercise avoidance.